Poster for the 3rd Annual Folklife Festival of Newfoundland and Labrador, Seeds to Supper. - Jarvis, Dale Gilbert
Poster for the 3rd Annual Folklife Festival of Newfoundland and Labrador, Seeds to Supper; presented by the Heritage Foundation of Newfoundland and Labrador, and to be held August 13-21, 2011 in St. John's. "Celebrating Agricultural Traditions Past and Present."